SARS-COV-2: GENETIC VARIABILITY, MUTATIONS AND VARIANTS OF CONCERN FOR THE GLOBAL WORLD - Ćupić, Maja (Medicinski podmladak, 2021)
Since emerging from Wuhan, China, in December of 2019, the novel coronavirus named SARS-CoV-2 has been causing devastating severe respiratory infections in humans worldwide.The new emerging disease was called COVID-19 and as early as the beginning of 2020 the world found itself in a COVID 19 pandemic. Despite the slow evolutionary rate of SARS-CoV-2 relative to other RNA viruses, its massive and rapid transmission during the COVID-19 pandemic has enabled it to acquire significant genetic diversity since it first entered the human population. This led to the emergence of numerous variants, some of them recently being labeled “variants of concern” (VOC). Emerging SARS-CoV-2 variants can be problematic if one or more of the independent mutations result in changes that make the virus more pathogenic, resistant to treatment, able to escape vaccines, or able to evade diagnostic tests.So far, there are four globally recognized VOCs (Alpha or B.1.1.7, Beta or B.1.351, Gamma or P.1 and newly recognized as VOC Delta or lineage B.1.617.2, and areas of the emerging variant of concern first time observed are United Kingdom, South Africa, Brazil, and India, respectively.Notable variants are those that contain mutations within the S gene, particularly within the region that codes for the receptor-binding domain (RBD) that recognize and attachte the specific ACE2 cell receptor. These mutations are responsible for increased viral transmission and influence disease severity, reliability of clinical tests as well as vaccine and therapy efficacy.VOCs characteristics and their mutational patterns, indicating the necessity of permanently close monitoring on a global level.
Keywords: mutational petterns; main variant of concern; SARS-CoV-2; COVID-19; B.1.1.7; B.1.351; P.1; B.1.617